The Effect Of Supplementary Feeding (PMT) Of Red Bean Extract On The Body Weight Of Pregnant Women With Chronic Energy Deficiency (CED) In The Working Area Of Way Urang Health Center, South Lampung Regency - Sy. Lubna; Elsy Juni Andri Kariny; Wulan Dari; Yuni Sulistiawati (Jurnal EduHealth, 2024)
Chronic Energy Deficiency (CED) in pregnant women increases the risk of delivery complications, maternal mortality, and fetal health problems such as LBW, prematurity, and birth defects. The prevalence of CED in Lampung Province for ages 15-49 years was 5142 cases, with cases in South Lampung Regency totaling 746 cases or 14.5%, ranking third highest among 15 Regencies in Lampung Province. To improve the nutritional status of pregnant women with CED, Supplementary Food Provision (PMT) needs to be given to pregnant women. Red bean extract is rich in protein, iron, and fiber which helps improve the nutritional status of pregnant women with CED. This study aims to determine the effect of Supplementary Food (PMT) red bean extract on the body weight of pregnant women with CED. This is a quantitative research with pre-experimental design with one group pretest-posttest design. A sample of 20 people was taken by Total sampling with the method of giving red bean extract 2x1 in the morning and afternoon for 14 days. This research was conducted in the working area of Way Urang Health Center. Data collection used observation sheets, and analysis used paired T-test. Based on the research results, the average body weight of pregnant women with CED before being given red bean extract was 48.62 kg and after being given red bean extract became 49.45 kg. Thus showing there is an effect of supplementary feeding of red bean extract on weight gain in pregnant women with CED in the working area of Way Urang Health Center, South Lampung Regency with p-value = 0.000. Pregnant women are expected to consume red bean extract regularly as a source of protein and iron to increase body weight and nutritional status of mothers with CED.